Scenario Planning of Kuala Kencana Sub-District Proliferation, Mimika Regency Central Papua Province - Yusi Eva Batubara; Sulthon Rohmadin (PT FORMOSA CENDEKIA GLOBAL, 2023)
A sub-district with a Camat as its leader is not an ordinary organization that carries out a certain field of government affairs. But they are responsible for a work area and its contents, namely society and its activities. The Camat's workload is closely related to the size of the area, the number of people served, and their distribution. Kuala Kencana sub-district has an area of 860,74 km2 with a population of 27,774 people, making it one of the most densely populated sub-districts in Mimika Regency. You can imagine how hard the task is, coupled with the relatively limited transportation and communication facilities and infrastructure. As a result, many people are not served properly. One way out is to split the sub-district into two so that the coverage area and population served are smaller. On the other hand, the number of ASN serving them increases. This study uses an exploratory method by operationalizing the concept of scenario planning. The stages are Identify Focal Issue (Focal Concern) or Decision; Identify Key Forces; Identify Driving Forces (change drivers); Identify Uncertaint); Selecting the Scenario Logic; Fleshing Out the Scenario. The research produced three scenarios. The normal scenario for the Proliferation of the Kuala Kencana Sub-district followed PP 17 of 2018 regulations; the above normal scenario for the Proliferation of the Sub-district was carried out with the support of affirmative policies from the Central Government. In the sub-normal scenario, the village/village administrative proliferation is carried out first before the sub-district Proliferation